Ardisianone, a natural benzoquinone, efficiently induces apoptosis in human hormone‐refractory prostate cancers through mitochondrial damage stress and survivin downregulation. Issue 2 (5th June 2012) - Yu, Chia‐Chun; Wu, Ping‐Jung; Hsu, Jui‐Ling; Ho, Yunn‐Fang; Hsu, Lih‐Ching; Chang, Yu‐Jia; Chang, Hsun‐Shuo; Chen, Ih‐Sheng; Guh, Jih‐Hwa
Abstract BACKGROUND Increasing evidence suggests that mitochondria play a central role in regulating cell apoptosis. Survivin, an inhibitor of apoptosis protein (IAP) family member, mediates resistance to cancer chemotherapy particularly in prostate cancers. Therefore, development of anticancer agents targeting mitochondria and survivin is a potential strategy. METHOD Cell proliferation was examined by sulforhodamine B, CFSE staining, and clonogenic assays. Mitochondrial membrane potential (ΔΨm) and reactive oxygen species (ROS) were detected by flow cytometric analysis. Protein expression was detected by Western blot. RNA levels were examined by reverse transcription polymerase chain reaction assay. Overexpression of constitutively active Akt was also used in this study. RESULTS Ardisianone, a natural benzoquinone derivative, displayed anti‐proliferative and apoptotic activities against human hormone‐refractory prostate cancer cells (HRPC), PC‐3, and DU‐145. Ardisianone dramatically induced mitochondrial damage, identified by downregulation of Bcl‐2 family proteins, ROS production, and loss of ΔΨm. Ardisianone also inhibited Akt and mTOR/p70S6K pathways and induced a fast downregulation of survivin, leading to activation of mitochondria‐involved caspase cascades. Overexpression of constitutively active Akt partly rescued ardisianone‐mediated apoptotic signaling cascades. Furthermore, a long‐term treatment of ardisianone caused an increase of endoplasmic reticulum (ER) stress, upregulation of cIAP1 and cIAP2, and apoptosis‐inducing factor (AIF)‐mediated caspase‐independent apoptosis. CONCLUSIONS The data suggest that the ardisianone induces apoptosis in human prostate cancers through mitochondrial damage stress, leading to the inhibition of mTOR/p70S6K pathway, downregulation of Bcl‐2 family members, degradation of survivin, and activation of caspase cascades. The data provide evidence supporting that ardisianone is a potential anticancer agent against HRPCs. Prostate 73: 133–145, 2013. © 2012 Wiley Periodicals, Inc.